Research on the Establishment of Party Building Demonstration and Quality Improvement in Aerospace Vocational Colleges in the New Era - Zheng, Mengqi (Journal of Educational Research and Policies, 2025)
This article aims to explore the path and strategies for the establishment of party building demonstration and quality improvement in aerospace vocational colleges under the background of the new era. Based on the overall requirements of Party building in the new era, this paper analyzes the current situation and challenges of Party building work in aerospace vocational colleges, and combines the cases of Party building at Beihang University and Soochow University to propose specific demonstration and quality improvement measures such as strengthening political leadership, improving institutional mechanisms, innovating work methods, strengthening team building and Party member education, emphasizing demonstration guidance and career development, in order to enhance the overall level of Party building work in aerospace vocational colleges.